Mammalian‐Like Inflammatory and Pro‐Resolving Oxylipins in Marine Algae. (5th May 2020) - Jagusch, Hans; Baumeister, Tim U. H.; Pohnert, Georg
Abstract: Oxylipins constitute a family of oxidized fatty acids, that are well known as tissue hormones in mammals. They contribute to inflammation and its resolution. The major classes of these lipid mediators are inflammatory prostaglandins (PGs) and leukotrienes (LTs) as well as pro‐resolving resolvins (Rvs). Understanding their biosynthetic pathways and modes of action is important for anti‐inflammatory interventions. Besides mammals, marine algae also biosynthesize mammalian‐like oxylipins and thus offer new opportunities for oxylipin research. They provide prolific sources for these compounds and offer unique opportunities to study alternative biosynthetic pathways to the well‐known lipid mediators. Herein, we discuss recent findings on the biosynthesis of oxylipins in mammals and algae including an alternative pathway to prostaglandin E2, a novel pathway to a precursor of leukotriene B4, and the production of resolvins in algae. We evaluate the pharmacological potential of the algal metabolites with implications in health and disease. Abstract : The uniqueness of oxylipin endowment in mammals is cracked by marine algae. They also form bioactive lipid mediators such as prostaglandins (PGs), leukotrienes (LTs), and resolvins (Rvs) in response to wounding as is observed in mammals. Contributions to the algal oxylipin chemistry kicked off the discovery of novel biosynthetic pathways in mammals with implications in health and disease.